2023
DOI: 10.1088/1755-1315/1169/1/012091
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of antioxidant and hedonic acceptance of turmeric extract-enriched milk

Abstract: Since COVID-19 pandemic, there was an increasing of people adopting a healthy lifestyle through health supplement and functional foods. This study aimed to develop turmeric milk which has high antioxidant activity that can be accepted by the community. The difference in the concentration of turmeric powder added (0.9%, 1.9%, and 2.8%) was carried out to determine the antioxidant activity by DPPH method and the curcumin level by HPLC method. Hedonic tests were used to evaluate the effect of turmeric powder into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…However, this deviation of those attributes from the ideal value is not penalised with a significant decrease in acceptance. This is contrary to the results of a study of the addition of turmeric to milk [79] where it was concluded that turmeric supplement leads to a decrease in consumer preference because of their dark yellow colour. Despite expectations, none of texture attributes significantly affected the decrease in overall liking.…”
Section: Just-about-right (Jar) and Penalty Analysiscontrasting
confidence: 98%
“…However, this deviation of those attributes from the ideal value is not penalised with a significant decrease in acceptance. This is contrary to the results of a study of the addition of turmeric to milk [79] where it was concluded that turmeric supplement leads to a decrease in consumer preference because of their dark yellow colour. Despite expectations, none of texture attributes significantly affected the decrease in overall liking.…”
Section: Just-about-right (Jar) and Penalty Analysiscontrasting
confidence: 98%